Mixed gas sources induced co-existence of sI and sII gas hydrates in the Qiongdongnan Basin, South China Sea. (June 2021) - Wei, Jiangong; Wu, Tingting; Zhu, Linqi; Fang, Yunxin; Liang, Jinqiang; Lu, Hailong; Cai, Wenjiu; Xie, Zhiyuan; Lai, Peixin; Cao, Jun; Yang, Tianbang
Abstract: Crystal structure and gas source are two important aspects in studying natural gas hydrate systems. In 2018, Guangzhou Marine Geological Survey carried out its fifth natural gas hydrate drilling expedition (GMGS5) in the Qiongdongnan basin of the South China Sea. In this paper, analyses of gas composition, stable carbon isotopes and Raman spectroscopy were conducted on twelve gas hydrate samples recovered at drill site W08, at depths of 17–170 m below seafloor. The results show that the main component of the hydrate-bound gas is methane (72.5–97.5%), mixed with other hydrocarbon gases (ethane: 1.9–12.1%, propane: 0.1–11.3%, i-butane: 0.0–3.5%, n-butane: 0.0–0.2% and C5+ : 0.0–0.2%). The δ 13 C of methane, ethane and propane in the hydrate-bound gases are −63.6 −51.9‰, −29.2 −26.6‰ and −25.6 −23.7‰, respectively. The hydrate-bound gas is inferred to be a mixture of microbial and thermogenic gases. Raman spectroscopic analysis indicates that structure I and structure II gas hydrates co-exist in the samples. Structure II gas hydrate is increasingly being discovered in the South China Sea, and it is suggested that natural gas hydrate resources might be underestimated and need to be re-evaluated. Highlights: Gas hydrates were sampled from multiple strata by drilling in the Qiongdongnan Basin in the South China Sea. Gas compositions and isotopic analyses show the hydrate-bound gases are of mixed origin. Raman spectroscopic analysis shows the coexistence of sI and sII gas hydrates.